2014
DOI: 10.1073/pnas.1413318111
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of long-range order in sheets of magnetic dimers

Abstract: Quantum spins placed on the corners of a square lattice can dimerize and form singlets, which then can be transformed into a magnetic state as the interactions between dimers increase beyond threshold. This is a strictly 2D transition in theory, but real-world materials often need the third dimension to stabilize long-range order. We use high pressures to convert sheets of Cu 2+ spin 1/2 dimers from local singlets to global antiferromagnet in the model system SrCu 2 (BO 3 ) 2 . Single-crystal neutron diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
27
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 32 publications
1
27
0
Order By: Relevance
“…In simpler words, our results also suggest that pressures of the order of a few gigapascals might be used to control the J′=J parameter through the pantograph effect and therefore to drive SCBO out of the spin dimer ground state into plaquette or Néel order. Magnetic susceptibility vs. pressure and very recent neutron diffraction under pressure results (30,31) support these ideas. We also note that low temperature active Raman modes have been identified as being correlated with the spin gap in SrCu 2 (BO 3 ) 2 (32).…”
Section: Discussionmentioning
confidence: 86%
“…In simpler words, our results also suggest that pressures of the order of a few gigapascals might be used to control the J′=J parameter through the pantograph effect and therefore to drive SCBO out of the spin dimer ground state into plaquette or Néel order. Magnetic susceptibility vs. pressure and very recent neutron diffraction under pressure results (30,31) support these ideas. We also note that low temperature active Raman modes have been identified as being correlated with the spin gap in SrCu 2 (BO 3 ) 2 (32).…”
Section: Discussionmentioning
confidence: 86%
“…In an X-ray diffraction investigation the temperature dependence of the lattice parameters was analysed as an indirect proxy for the singlet triplet gap leading to the suggestion that it closes at 20 kbar 23 . At even higher pressures neutron and X-ray diffraction experiments observed a transition above 45 kbar from the ambient I42M tetragonal space group to monoclinic [24][25][26] .…”
mentioning
confidence: 98%
“…The magenta line shows the tetragonal to monoclinic structural transition 25 . The corresponding monoclinic space groups are indicated 26,27 . The dashed line in the plaquette phase is the extrapolated energy gap using Ref.…”
mentioning
confidence: 99%
“…Pressure is a tool of choice to tune magnetic couplings and thereby enables to explore the Shastry-Sutherland phase diagram for which SrCu 2 (BO 3 ) 2 is the only known spin S ¼ 1=2 realization. Previous studies [17][18][19][20] have indicated that pressure actually drives the compound even closer to a magnetic quantum phase transition.…”
Section: Introductionmentioning
confidence: 95%
“…Strong magnetoelastic effects are observed upon entering the spin-gap regime (T $ 35 K) [22]. These magneto-elastic effects have been used in combined pressure and temperature dependent X-ray diffraction measurements to detect signs of quantum phase transitions [20]. There, a change in the compressibility of the a-axis was recorded around 4.5 GPa at 4 K. Applying an additional external magnetic field of 7 T magnetic ordering has been reported below 4 K at 2.4 GPa by NMR measurements [18].…”
Section: Introductionmentioning
confidence: 99%